2004
DOI: 10.1089/153056204773644625
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Readiness for Telehomecare: Implications for Implementation

Abstract: Numerous pilot studies have demonstrated that telehomecare technology may improve client outcomes through timely intervention and health crises prevention, thereby reducing return visits to hospitals and physician offices. Although the potential of telehomecare to increase access to services and improve quality of care and health outcomes is recognized, expectations for its widespread adoption have not been realized. Factors affecting diffusion of innovations include, among other things, perceptions of the tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 10 publications
(9 reference statements)
0
15
0
Order By: Relevance
“…While government-led telehealth initiatives tend to focus on video conferencing, a number of small studies and pilot projects delivering health services via the Internet have been reported in patients with breast cancer (21,22), asthma (23), chronic obstructive pulmonary disease (24,25), diabetes (26)(27)(28)(29)(30)(31)(32), lung transplantation (33), overweight (34)(35)(36)(37)(38)(39)(40), smokers (41), chronic heart failure (25,(42)(43)(44) and CVD (45)(46)(47)(48). These studies demonstrated that patients were willing to enter self-measured data online and communicate with health care providers via e-mail and/or chat/video conferencing.…”
Section: Discussionmentioning
confidence: 99%
“…While government-led telehealth initiatives tend to focus on video conferencing, a number of small studies and pilot projects delivering health services via the Internet have been reported in patients with breast cancer (21,22), asthma (23), chronic obstructive pulmonary disease (24,25), diabetes (26)(27)(28)(29)(30)(31)(32), lung transplantation (33), overweight (34)(35)(36)(37)(38)(39)(40), smokers (41), chronic heart failure (25,(42)(43)(44) and CVD (45)(46)(47)(48). These studies demonstrated that patients were willing to enter self-measured data online and communicate with health care providers via e-mail and/or chat/video conferencing.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a limited consensus on identified barriers and categories. This limited agreement about what can be expected from the adoption of those systems could be one of the reasons for the delay in the adoption of HIS (Hebert and Korabek 2004;Gruber et al 2009;Williams et al 2003). There is also a large number of studies that focus on a particular set of stakeholders' groups, namely, healthcare professionals, GPs, managers and policymakers.…”
Section: Motivationmentioning
confidence: 99%
“…It is thus important for project managers to assess telehomecare readiness within all groups of stakeholders in order to identify potential barriers to the integration of the technology into current practices. 7,29 Healthcare organizations Assessment of the particular characteristics of organizations involved in telehomecare projects and their environment is needed to prepare and to support changes. This requires a close look at the various constraints related to real-life settings.…”
Section: Project Managersmentioning
confidence: 99%
“…[3][4][5][6] Although the potential of telehomecare to increase access to services and improve quality of care and health outcomes is recognized, its widespread adoption has not been realized yet. 7 Telehealth seems particularly appropriate for vulnerable populations. Vulnerable populations consist of, but are not limited to, citizens who face particular risks for their health and well-being because of economic, sociodemographic, ethnic, cultural, geographical, physical, and/or mental health status.…”
Section: Introductionmentioning
confidence: 99%